Alternation vs. Allomorphic Variation in Old English Word-Formation: Evidence from the Derivational Paradigm of Strong Verbs - Urraca, Carmen Novo; Fernández, Laura Pesquera (Studia Anglica Posnaniensia, 2015)
This article addresses the question of Old English alternations with a view to identifying instances of allomorphic variation attributable to the loss of motivation and the subsequent morphologization of alternations. The focus is on the strong verb and its derivatives, in such a way that the alternations in which the strong verb partakes can be predicted on the basis of phonological principles, whereas allomorphic variation with respect to the strong verb base is unpredictable. Out of 304 derivational paradigms based on strong verbs and comprising 4,853 derivatives, 478 instances have been found of phonologically motivated vocalic alternations. The conclusion is reached that the most frequent alternations are those that have /a/ as source and those with /y/ as target, because /a/ is the point of departure of i-mutation and /y/ its point of arrival. Sixteen instances of allomorphic variation have also been found, of which /e/ ~ /eo/, /e/ ~ /ea/ and /i/ ~ /e/ are relatively frequent.